WHAT DO PEOPLE DO TO SUSTAIN A CONVERSATION: ANALYSIS OF THE FEATURES AND THE SPEECH FUNCTION OF A CASUAL CONVERSATION - Latifa Ika Sari; Ria Hermina Sari (University of Kuningan, 2020)
Conversation Analysis (CA) has a great implication in the second or foreign language teaching and learning. This study was aimed to analyse a casual conversation, to identify what people do to sustain a conversation. The conversation, which lasted for 20 minutes and involved three speakers, was transcribed verbatim. Several features of the spoken text are analysed: spontaneity, interactivity, interpersonal features, coherence features, negotiation of meaning, and speech function. The result of the analysis showed that there are several strategies used by the speakers: time-gaining strategies (filled pauses; frequent use of conjunctions: and, but, so); using chunks and producing one clause or phrase in small ‘runs’; self-monitoring strategies (repetition, backtracking), and interactional strategies (backchanneling, showing amusement by laughing or chuckling, using certain discourse markers, hedges, vague language, showing empathy by completing and repeating each other’s utterances). The speakers also negotiate interpersonally and logico-semantically to keep the conversation going on. The equal number of rejoinders that each speaker produces indicates that they are willing to support each other to sustain the conversation. This study implies that when teaching speaking, English teachers should include communication strategies to achieve the goals of communication.Keywords: casual conversation; negotiation of meaning; speech function; strategies.